In Search of a Welcoming Environment for Religions in the “New Kazakhstan” - Kusack, Wade (The review of faith & international affairs, 2024)
After experiencing first-hand the limitations of an exclusively activist, “name and shame” approach to advocating for religious freedom in Central Asia, I learned about a different, relational model of building religious freedom and covenantal pluralism, which was pioneered by the Institute for Global Engagement (IGE) in Southeast Asia. In this essay I tell the story of how my organization, Love Your Neighbor Community (LYNC), has applied the IGE model in Kazakhstan.